2017
DOI: 10.1299/mej.16-00696
|View full text |Cite
|
Sign up to set email alerts
|

Completion of analytical model of active magnetic thrust bearings including asymmetric air gap field between mixed materials

Abstract: The electrodynamics of magnetic thrust bearings are characterized by an above-average dependency on the bearing materials. Axially directed fields render laminated stators and rotors ineffective. High induced voltages inside the magnetic core evoke eddy currents and opposing fields, which are compensated by an additional magnetizing current causing a significant delay between the measurable coil current and the force-related magnetic flux. The control dynamics are hampered and even though this effect can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In [34], it is shown that eddy currents have an even lesser influence for SMCs. In addition, [35] showed a low influence of eddy currents with SMC materials. Therefore, the electric part of the electromagnet is described in Equation (3) [29], where u amp is the resulting load voltage of the amplifier.…”
Section: Amplifiermentioning
confidence: 93%
“…In [34], it is shown that eddy currents have an even lesser influence for SMCs. In addition, [35] showed a low influence of eddy currents with SMC materials. Therefore, the electric part of the electromagnet is described in Equation (3) [29], where u amp is the resulting load voltage of the amplifier.…”
Section: Amplifiermentioning
confidence: 93%